2006
DOI: 10.1021/jo061754k
|View full text |Cite
|
Sign up to set email alerts
|

Tripodal, Cooperative, and Allosteric Transphosphorylation Metallocatalysts

Abstract: Three artificial amino acids derived from l-serine by replacing the hydroxyl moiety with 1,4,7-triazacyclononane, 1,5,9-triazacyclododecane, and 1,4,7,10-tetraazacyclododecane, respectively, have been connected to the three arms of the tetraamine tris(2-aminoethyl)amine, Tren, to obtain tripodal ligands. They are able to bind up to four metal ions (like CuII and ZnII), three with the polyazamacrocycles and one with the Tren platform. Some of the ZnII complexes of these tripodal ligands proved to be good cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…In this work, we prepared mixed SAMs composed of thiol 1 ,32 containing a triazacyclononane (TACN) head group that forms a stable complex with Zn II ‐ions, and thiol 2 ,39 containing a TEG head group that renders the NPs soluble in aqueous solution (Scheme ). Previously, we have shown that multivalent systems, such as tripodal ligands,40 dendrimers,4143 and Au NPs,15 that contain multiple copies of the TACN⋅Zn II ‐complex are highly efficient catalysts for the transphosphorylation of HPNPP. For all systems, kinetic Zn II titrations revealed that catalysis requires the cooperative action of two TACN⋅Zn II complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we prepared mixed SAMs composed of thiol 1 ,32 containing a triazacyclononane (TACN) head group that forms a stable complex with Zn II ‐ions, and thiol 2 ,39 containing a TEG head group that renders the NPs soluble in aqueous solution (Scheme ). Previously, we have shown that multivalent systems, such as tripodal ligands,40 dendrimers,4143 and Au NPs,15 that contain multiple copies of the TACN⋅Zn II ‐complex are highly efficient catalysts for the transphosphorylation of HPNPP. For all systems, kinetic Zn II titrations revealed that catalysis requires the cooperative action of two TACN⋅Zn II complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticle concentration is expressed as ac oncentration of the TACN head groups on the surface of the gold nanoparticles. [34] Determination of surface saturationconcentration (SSC)…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…[190] Five years later he was able to follow up on this by reporting on a modified catalyst 153 (Scheme 97) whose transphosphorylation activity could also be controlled by zinc(II) ins in a positively cooperative manner. [191] Another class of oligodentate ligands with multiple metal binding sites was developed by Shinkai. The activity of his catalyst 154 in H 2 O/EtOH (2:1) was also found to depend on the presence of zinc(II) ions acting as a positive allosteric effector (Scheme 98).…”
Section: Allosteric Control Of Reactivitymentioning
confidence: 99%